2019
DOI: 10.1080/09537287.2019.1582818
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and effectiveness of knowledge management systems in SMEs

Abstract: This paper proposes a 3D fuzzy logic methodology to assess the efficiency and effectiveness of knowledge management systems (KMSs) adopted by small and medium enterprises (SMEs) and identifies a classification bringing together the behaviour of SMEs when adopting KMSs. The proposed methodology was previously tested on an individual SME and then implemented on a sample of SMEs. The results highlight that there is an ample variety of behaviours related to the nature of knowledge and the KMSs used. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 54 publications
(31 reference statements)
1
62
0
2
Order By: Relevance
“…In this perspective, Kim [73] reviewed KM practices within the context of SMEs, underscoring the importance of such practices on the economic-financial, market, technical, human, and, overall, organizational performances. However, considering the high complexity and integration of KM processes, linking culture, people, finance, technology, and organizational structures [12], the literature demonstrated that SMEs are often characterized by inefficient or ineffective behaviours when engaging in KM practices and/or tools [77].…”
Section: Knowledge Management (Km) For Economic Sustainability In Smesmentioning
confidence: 99%
“…In this perspective, Kim [73] reviewed KM practices within the context of SMEs, underscoring the importance of such practices on the economic-financial, market, technical, human, and, overall, organizational performances. However, considering the high complexity and integration of KM processes, linking culture, people, finance, technology, and organizational structures [12], the literature demonstrated that SMEs are often characterized by inefficient or ineffective behaviours when engaging in KM practices and/or tools [77].…”
Section: Knowledge Management (Km) For Economic Sustainability In Smesmentioning
confidence: 99%
“…Knowledge management has captured the attention of researchers in the knowledge-based economy [22], with interest in this academic and practice-oriented discipline witnessing a significant rise in recent years [23][24][25]. There is also a need nowadays to gain additional insight into how knowledge management is evolving within the context of public sector organizations [26], including social work organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Com o tempo, o conhecimento também é transformado em outras manifestações, tais como livros, tecnologia, práticas e tradições, o que ocorre em organizações de todos os tipos e na sociedade em geral. Quando utilizado de forma adequada, o conhecimento leva ao aumento da eficácia (Centobelli, Cerchione & Esposito, 2017). Assim, o conhecimento é um ato inerente ao ser humano, porém, para que este se desenvolva da forma tácita para a explícita, ou seja para que possa evoluir do individual para o coletivo (organizacional), é necessária a instituição de processos que visam justamente operacionalizar este caminho (Nonaka & Takeuchi, 1997;Ferraresi & Santos, 2014e Nonaka & Toyama, 2007.…”
Section: Gestão Do Conhecimentounclassified